Efforts to Increase Interest in Learning Practical Basics of Electronics through the Project Base Learning Learning Model for Class X Students in Audio Video Engineering 2 at SMK Negeri 2 Samarinda - Makkan, Abdullah (Educationist: Journal of Educational and Cultural Studies, 2022)
This study aims to increase students' interest in learning through the application of Project Based learning learning models in the Audi Video Engineering class at SMK Negeri 2 Samarinda. This research is a classroom action research conducted from April to June 2022. The subjects of this research are class X Engineering students. Audio Video 2 at SMK Negeri 2 Samarinda totaled 10 people, consisting of 10 males. The data in this study were collected using a learning outcome test which was assessed based on indicators of interest in learning the concepts of basic electronics. The completeness of student learning outcomes is by comparing the basic score with the Daily Test I and Daily Test II on the basic material of electronics. After conducting research with two cycles, the application of the Project Based learning learning model can increase interest in learning audio video techniques where at the end of the first cycle of action there are 6 students who have completed or 68.42% with an average student learning outcome or student understanding of 69.08, then increased in the second daily test with the number of students who completed 8 or 84.21% with the average student learning outcomes or concept understanding increased to 82.89 at the end of the second cycle of action. understanding of how the basics of electronics work for students of class X audio video engineering at SMK Negeri 2 Samarinda.